Development of a patient‐reported outcome instrument to assess complex activities of daily living and interpersonal functioning in persons with mild cognitive impairment: The qualitative research phase. Issue 1 (13th June 2015) - Gordon, Mark Forrest; Lenderking, William R.; Duhig, Amy; Chandler, Julie; Lundy, J. Jason; Miller, David S.; Piault‐Louis, Elisabeth; Doody, Rachelle S.; Galasko, Douglas; Gauthier, Serge; Frank, Lori
Abstract: Introduction: As drug development research efforts move toward studying patients earlier in the course of Alzheimer's disease (AD), it is important to incorporate the patient's perspective into measurement of outcomes. Methods: This article summarizes the qualitative work of the Patient‐Reported Outcome Consortium's Cognition Working Group in the development of a new self‐reported outcome measure in persons with mild cognitive impairment (MCI) due to suspected AD, herein referred to as MCI. Results: The draft measure captures the patient's voice for two functional domains, complex activities of daily living and interpersonal functioning. Discussion: This work represents a series of initial steps in the development of this rating scale. The next steps are to conduct psychometric analysis and evaluate the role of insight.